Antioxidant Properties And Glucan Compositionof Various Crude Extract From Lentinus Squarrosulus Mycelial Culture - Rahayu Ahmad; Sutha Muniandy; Nur Iffah Abdullah Shukri; Siti Mariatul Usyida Alias; Aidil Abdul Hamid; Wan Mohtar Wan Yusoff; Sahidan Senafi; Fauzi Daud (Scientific Research, 2024)
Various crude extracts of Lentinus squarrosulus mushroom mycelium and culture broth were prepared for antioxidant studies, glucan and carbohydrate compound analysis. Crude extract from ethanol, cold and hot water extraction was tested on several complementary test systems namely DPPH free radical scavenging, β-carotene linoleic acid oxidation, total phenolic compound, total flavonoid compound, total carbohydrate content and total glucan compositions. The antioxidant activity of the crude extracts of Lentinus squarrosulus mushroom mycelium and culture broth was determined by 2,2’ diphenyl-1-picrylhydrazyl (DPPH) radical scavenging method and β-carotene linoleic acid assay. Crude extracted from culture broth EPS EE recorded the highest radical scavenging effects at 20 mg/mL (85%) which is closer to the control antioxidants (ascorbic acid 97%; BHT 92.4%; BHA 93.6%). Both the ethanol extract (IPS EE and EPS EE) exhibited the highest β-carotene linoleic acid oxidation by recording IC50 values of 0.6 and 0.65 mg/mL respectively. IPS EE (0.59 mg/g) and EPS WE (0.58 mg/g) showed high flavonoid content whereas total phenol content was high in EPS WE (0.85 mg/g) and IPS EE (0.84 mg/g). Total carbohydrate concentrations were high in IPS HWE and IPS CWE with 19.1 and 16.3 mg/mL respectively and these data correlate with the β-glucan content in both extracts. The highest β-glucan content found in IPS CWE and IPS HWE were 12.2 and 11.4% w/w respectively.